Analysis of Non-clinical Risk Factors for Heart Disease and Stroke Using Statistical Method - Sri Sumarlinda; Azizah Binti Rahmat; Zalizah Binti Awang Long (LPPM Universitas Duta Bangsa Surakarta, 2022)
Heart disease and stroke are the main contributions to health disorder. Two factors influence the susceptibility of the disease, namely clinical risk factors and non-clinical factors. This study aims to analyze the effect of non-clinical risk factors on the susceptibility to heart disease and stroke. The non-clinical risk factors are stress management, age, obesity, genetics, smoking, gender, lifestyle (nutrition), lifestyle (timing rest), and physical activity. Analysis of the influence of non-clinical risk factors on susceptibility using statistical methods, namely descriptive statistics, normalization tests with the Kolmogorov-Smirnov test, validity tests, reliability tests, and correlation tests. The descriptive statistical tests show that the risk factors for stress management, obesity, and smoking have a more significant influence than others. While Gender and physical activity have more negligible effect than others. Testing with one sample Kolmogorov-Smirnov Test shows that the data is normally distributed. Validity testing produces 100% valid data. The reliability test using Cronbach's alpha of 9 non-clinical risk factor items resulted in a value of 0.684, which means reliable. Correlation test between 9 items of non-clinical risk factor shows significant between items.